Notes on some corydiid species from China, with the description of a new genus (Blattodea: Corydioidea: Corydiidae). Issue 3 (4th May 2019) - Qiu, Lu; Yang, Zhi-Bin; Wang, Zong-Qing; Che, Yan-Li
Summary: This article presents the diversity of cockroach family Corydiidae from China. Epipolyphaga wukong Qiu, Che et Wang, n. gen., n. sp ., is described. Habitus and detailed characters of the new taxa are illustrated. A comparison between the new genus and the morphologically similar genus Eupolyphaga Chopard is given. The genus Tivia Walker and the species Eucorydia westwoodi (Gerstaecker) are newly recorded from China. The Corydioidea chapter in Cockroaches of Southeastern China by Liu et al. is revised. A key to genera and a checklist of Chinese Corydiidae are provided.